Evaluación clínica comparativa del tratamiento de la periodontitis moderada o severa con y sin aplicación local de Tetraciclina (HCL) (1996)
ABSTRACT: This report compares an inductive technique for the surgical treatment of moderate or severe periodontitis with a similar technique, performed on the opposite side, where a topical application of Tetracycline (HCL) is used, over instrumented roots. This research were on ten patients between 28 and 50 years of age, (mean age: 34 years) and the following biometric measures were taken: plaque index, gingival index, percentage of bleeding and clinical attachment level. Flap curettage with or without topical application of tetracycline (HCL) were done on random sextants. This were registrated on baseline and 12 months. Statiscally data were analized based in the proof of combined median using as an statistics the square chi. The results showed that between 0 and 12 months there were significant differencies between test (T.G.) and control (C.G.) groups, for plaque index (P.I.) gingival index (G.I.) and percentage of bleeding (%B), without a tendencie to any group, because the probabilities are equal to both. On clinical attachment level (C.A.L.) in the mesial region the results showed significant difference between both groups but that difference is favorable to the T.G. since the associated probability is smaller. Distal region showed difference statiscally significants to the T.G. but not to the C.G. Changes on C.A.L. in the medium region were no stadistically significants to any group. Analized data sugggest a tendencie to obtain again in C.A.L.. thorough time on the T.G. and C.G. with a light favorable difference to the T.G., although not statistically significant.